Strengthening Sustainable Entrepreneurship Through Trademark Legal Protection and Human Resource Management - Indrawati, Septi; Iftayani, Itsna; Widjajani, Susi (Universitas Muhammadiyah Magelang, 2026)
The programme was initiated in response to the low level of legal awareness among business actors regarding trademark registration and the suboptimal management of human resources in business operations. These conditions potentially create legal vulnerability and managerial inefficiency that may affect business sustainability. This program aimed to enhance the knowledge and capacity of business actors in trademark legal protection and human resource management as strategic instruments for sustainable business development. The program employed an educative-participatory approach through legal counselling, management training sessions, interactive discussions, and administrative assistance. The trademark protection material was delivered in accordance with Law Number 20 of 2016 concerning Trademarks and Geographical Indications, particularly emphasizing the constitutive (first to file) principle in the trademark registration system. The results indicate an increased understanding among participants regarding the urgency of trademark registration as a form of intangible asset protection, as well as improved awareness of the importance of organizational structure, task division, and standard operating procedures in business management. Overall, the GERATAMA program produced an integrative legal-economic empowerment model by combining legal strengthening and managerial capacity building. This model contributes to the development of entrepreneurship that is economically growing, legally secure, and professionally managed, and it holds potential for replication in other community-based business groups with similar characteristics.